C35 SUCCESSFUL PERCUTANEOUS TREATMENT OF A GIANT CORONARY ANEURYSM IN THE EMERGENCY SETTING. (18th May 2022) - Quadri, G; Tomassini, F; Rolfo, C; Franzè, A; Cerrato, E; Chinaglia, A; Tizzani, E; Minniti, D; Varbella, F
Abstract: In 2008, a 60–year–old man with an anterior STEMI and cardiogenic shock underwent coronary angiography: a thrombotic occlusion in the mid–LAD, distal to a coronary aneurysm, was successfully treated with DES. (Fig. A ). In 2020, the patient was readmitted with NSTE–ACS and cardiogenic shock. The coronary angiography showed severe stenosis after the proximal–LAD aneurysm and occlusion of the previously implanted stent (Fig. B, Panel B1 and B3 ). A very slow distal coronary flow was provided by a huge epicardial collateral branch emerging from a second giant coronary aneurysm; furthermore, a severe stenosis in the proximal–LCX was present (Fig. B. Panel B1, 2 ). The patient was judged inoperable by the cardiac surgeon. After IABP positioning, a DES was implanted in the LCX. The LAD was then approached. TIMI 3 flow was achieved after a challenging procedure requiring both coronary and peripheral interventional tools: 3 DES (yellow dotted–lines), 8 coronary and 1 peripheral covered stents (green solid–lines) and 6 coils were used to treat the stenosis and exclude the coronary aneurysms. (Fig. B, Panel B3, 4 ). Both DAPT and oral anticoagulation were prescribed at discharge. A 4–month coronary angiography confirmed the good procedural result. (Fig. C ). This case shows the unexpected enlargement of a coronary aneurysm through the years and the presence of a new uncommon epicardial communication, necessary to overcome a chronic coronary occlusion. It highlights the importance of knowing different interventional techniques and using non–conventional tools to approach complex coronary anatomies, such as aneurysmatic disease, whose treatment is often challenging, especially in complicated clinical scenarios.